ECOLOGY AND SUSTAINABILITY: Renewable Energy Centre Mithradham: A Model for Sustainable Development - Pittappillil, George Peter (Asian Horizons, 2012)
Ecology and sustainability are probably the most often used words in all common platforms. The reason is that the misuse of nature and its gifts are detrimentally affecting the whole human race without any distinction. The entire eco-system has slipped in to a crisis due to the widespread misuse of science and technology for the so called human development. Environment that was a source of happiness for us and our fellow creatures has now degraded, bringing insurmountable sorrow in our lives. This is the result of our unbridled desire for pleasures and the apparent short and seemingly easy path of development that we have taken. Evolution cannot stop or go in the reverse direction. The next phase of our human evolution should consciously take a cleaner path if we are to overcome this crisis. The cleaner path is not always the easy but the better and safer path.